“If I want to be able to keep going, I must be active.” Exploring older adults’ perspectives of remote physical activity supports: a mixed-methods study - Mehrabi, Samira; Drisdelle, Sara; Dutt, Hanna R; Middleton, Laura E (Frontiers in Public Health, 2024)
Introduction: Pandemic-related public health restrictions limited older adults’ physical activity programs and opportunities. Physical activity supports shifted to remote options, however, information on their adoption and effectiveness is limited. This study aims to describe the remote supports received by older adults and their perceived effectiveness. Additionally, it aims to describe facilitators and barriers to remote supports for physical activity among older adults, particularly those reliant on technology. Methods: This study used an explanatory, sequential, mixed-methods design. Community-dwelling older adults (≥ 60 years) were recruited to partake in a web-based survey and an optional semi-structured follow-up interview informed by the COM-B model. Participant characteristics, perceived effectiveness of remote supports, and the presence and severity of barriers were described. Changes in physical activity levels before and during the pandemic were analyzed using the Wilcoxon signed-rank test. Qualitative data underwent inductive thematic analysis. Results: 57 older adults (68.3±7.1 years, 43 Female) completed the survey, of which 15 participants (67.4±5.8 years, 12 Female) participated in interviews. The majority were Caucasian, highly educated, and resided in Canada. Total physical activity levels showed no statistically significant change from before to during the pandemic (p=0.74); however, at-home exercise participation and technology usage increased. Pre-recorded and real-time virtual exercise supports were perceived as most effective. Main barriers included limited contact with exercise professionals, limited access to exercise equipment or space, and decreased mental wellness. Thematic analysis identified five main themes: i) Enabled by knowledge and resources; ii) Diverse motivations for physical activity; iii) Fostering participation through social connection; iv) Supervision and safety: enabling adherence; and v) Virtual exercise: a sustainable option with technological considerations. Conclusion: Virtual platforms show promise in supporting older adults' physical activity at home, especially for those with limited in-person access. Our study suggests that both real-time and pre-recorded virtual exercise supports are feasible, depending on technological capacity and support. While interactive real-time virtual programs allow interaction with professionals and peers, pre-recorded programs provide timing flexibility. Further research is needed to establish best practices for safe and effective virtual exercise programming, promoting its long-term adoption for supporting a wider range of older adults.